Enjeux et limites de la notion de citoyenneté numérique en didactique des langues au regard du contexte des formations obligatoires dans le cadre du contrat d'intégration républicaine - Yuchen Chen; Caroline Venaille; Myriam Dupouy (ALSIC: Apprentissage des Langues et Systèmes d'Information et de Communication)
Within the framework of the French Office for Immigration and Integration (henceforth OFII), civic and language training courses are presented as prerequisites and necessary levers for integration under the contrat d'intégration républicaine (henceforth CIR) for adult signatories designated as "extra-European". Faced with this close link between migration and language policies, many studies criticise a standardised, asymmetrical training approach, with integration designed "for" rather than "with" (FLIC, 2011, Vadot, 2023). However, as far as we are aware, there is little research into what 'the' digital environment (Cappellini, 2021) would be in the context of the CIR. Based on the observation that the projects and contexts of students enrolled in language didactic training courses are changing, this exploratory research proposes to examine the transfer of the notion of education for digital citizenship to the field of language teaching and learning, and more particularly in the context of training aimed at an adult public and linked to migration policy issues. The study explores this particular use of 'citizenship', 'digital' and 'language', terms associated with a potentially reductive logic in relation to diverse, complex and dynamic practices. This contribution invites us to consider the political connotations of the polysemous term citizenship in the digital age and the limits of transferring digital citizenship education to the field of language teaching and learning, and more specifically to the specific framework of the CIR.